Modeling of lithium granule injection in NSTX using M3D-C1. (6th April 2017) - Fil, A.; Kolemen, E.; Ferraro, N.; Jardin, S.; Parks, P.B.; Lunsford, R.; Maingi, R.
Abstract: In this paper, we present simulations of pedestal control by lithium granule injection (LGI) in NSTX. A model for small granule ablation has been implemented in the M3D-C1 code (Jardin et al 2012 Comput. Sci. Discovery 5 014002), allowing the simulation of realistic lithium granule injections. 2D and 3D simulations of Li injections in NSTX H-mode plasmas are performed and the effect of granule size, injection angle and velocity on the pedestal gradient increase is studied. The amplitude of the local pressure perturbation caused by the granules is found to be highly dependent on the solid granule size. Adjusting the granule injection velocity allows one to inject more particles at the pedestal top. 3D simulations show the destabilization of high order MHD modes whose amplitude is directly linked to the localized pressure perturbation, which is found to depend on the toroidal localization of the granule density source.